Pengaruh kompetensi pedagogi guru terhadap prestasi belajar siswa pada mata pelajaran seni rupa kelas V SDN Jarakan Bantul Yogyakarta - Indrawan, Esa Muhammad ikhsan; Arief, Ardian (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
This article aims to analyze the influence and magnitude of the influence of teacher pedagogical competence on student learning achievement in fine arts subjects at SDN Jarakan Bantul. The approach used is quantitative correlation. The data subjects used were all grade V students of SDN Jarakan Bantul totaling 70 students. Sample data using non-probability sampling using saturated samples, ie all members of the population become research samples. Data collection techniques used questionnaire techniques to collect teacher pedagogical competence data and student report card documentation on learning achievement data. The data processing method uses descriptive analysis test, prerequisite analysis test (normality test, homogeneity test, and linearity test) and hypothesis testing using simple linear regression processed with SPSS version 26.0 software. The results of hypothesis testing with simple linear regression get a sig value. 0.041 (0.041 <0.05) so it is known that there is an effect of teacher pedagogical competence on student learning achievement. In addition, the magnitude of the effect obtained from simple linear regression in the regression equation is Y = 75,109 + 0.083X with the result that every 1% increase in variable X is 0.083 and will decrease by 0.083, because the regression coefficient value is positive (+), it can be interpreted that variable X has a positive effect on variable Y. It is also known that the result of R Square is 0.070 this value means that the effect of teacher pedagogical competence (X) on art learning achievement (Y) is 7% while 93% of art learning achievement is influenced by other variables that are not studied. Based on the results of data analysis of the research that has been done, it can be concluded that there is an influence between the pedagogical competence of teachers on the learning achievement of fine arts subjects of grade V students of SDN Jarakan Bantul